Research about two‐step channel with lateral narrowing structures in the flow mass transfer of proton exchange membrane fuel cell. Issue 3 (8th May 2022) - Li, J.R.; Wang, H.Y.; Lin, P.J; Wang, G.D.; Sun, J.C.; Yang, D.M.
Abstract: Proton exchange membrane fuel cell (PEMFC) is a new energy device with wide application prospects. The design of its flow field is one of the effective methods to improve its performance. As key parameters of the PEMFC, mass transport is directly dependent on these channels in flow fields. To enhance the mass transport in the channel, some simple two‐step structures with forced convection are proposed in previous research. But the convections formed by these simple structures are only in one direction. Compared to the complex flow behaviors of the gas in PEMFC, these one‐direction convections are not enough. Then the more comprehensive dimensional convections are made by a new kind of two‐step structure with lateral narrowing. The mathematical model of the new‐designed PEMFC is simulated by the Fluent module in the computational fluid dynamics software ANSYS. Compared with the parallel‐straight‐flow channel, the current density of the new channel proposed in this paper can be increased by 12.5%.